Disc Prolapses In The Spine on Magnetic Resonance Imaging: Disc Prolapses in the Spine on MRI - Tatheer Fatima, Syeda; John, Akash; Ali, Abid; Bakhtawar, Khadija; Aftab Ahmed, Aiman (Pakistan Journal of Health Sciences, 2022)
A disc herniation occurs when the nucleus, cartilage, or fragmented annular tissue are displaced outside the intervertebral disc area. Because of its high sensitivity and specificity for disc herniations, MRI is the method of choice for assessing disc morphology (both protrusions and extrusion).Objective: To use MRI to diagnose disc disorders, to create optimal MRI sequences for diagnosing spine pathologies, to detect which gender was affected, and to correlate the spinal disc with patient age.Methods:It was a descriptive cross-sectional study carried out in a DHQ Hospital, Gujranwala, Pakistan and the sample size for this research was 71 calculated via a convenient sampling approach. The data were collected in four months from December 2021 to March 2022 after informed consent. Patients who presented to the MRI department for spinal disc prolapse were included in this study. Patients were to be registered with age, gender, type of examination, and protocol used. An MRI scanner was made by a Japanese manufacturer (Toshiba). Data were analyzed using SPSS version 20. Results: Disc prolapse is widespread in older patients, with an average age of 41-50 years. Males are more likely than females to have disc prolapses 45(63.4 %). In approximately 50(70.4%) of patients, the sagittal and axial technique is the best for confirming disc prolapse. Lower back discomfort is the most prevalent complaint among patients.Conclusion: Disc prolapse is widespread in older male individuals. The sagittal and axial technique is the best for confirming disc prolapse. Lower back discomfort is the most prevalent complaint among patients.